Critical Analysis of a Technology-Based Enterprise: A Case Study of Yahoo! - Ahmad Naufal Aufa (Universitas Airlangga, 2018)
Yahoo’s history might give a valuable lesson about a critical issue in a leading company, which is now considered to no longer have a competitive advantage. This paper aims at analyzing critically the issues of Yahoo’s ruin. The findings suggest that the causes include having no superior product, lack of focus, poor leadership, and no clear vision. Consequently, this issue gave a massive impact on the company’s revenue, net profit, valuation, and even existence. Finally, although this case is about a high-tech company’s issue, this might become sort of evaluation and reflection for any companies, since the causes seem relevant to all company types. This case also can be a learning lesson for professionals, academicians, and students.